Cloud Computing for Enterprise Architectures - Mahmood, Zaigham; Hill, Richard (Springer eBooks., 2011)
An understanding of cloud technology innovation is becoming increasingly essential for IT practitioners, as entrepreneurs realise the business requirements fulfilment potential of an enterprise perspective of cloud computing. This important text provides a single point of reference for state-of-the-art cloud computing design and implementation techniques. The book examines cloud computing from the perspective of enterprise architecture, asking the question; how do we realize new business potential with our existing enterprises? Divided into four parts covering all aspects of cloud computing for enterprise architectures, the text introduces fundamental concepts and principles, examines approaches and frameworks for the adoption of cloud computing, explores existing issues and challenges, and presents future directions and ideas for further research. Topics and features: With a Foreword by Thomas Erl Contains contributions from an international selection of preeminent experts Presents the state-of-the-art in enterprise architecture approaches with respect to cloud computing models, frameworks, technologies, and applications Discusses potential research directions, and technologies to facilitate the realization of emerging business models through enterprise architecture approaches Provides relevant theoretical frameworks, and the latest empirical research findings Collecting together the latest theoretical, practical and evaluative work in the field, this authoritative reference can also be used as a primer for self-study. As such, it will appeal to a broad audience from enterprise architects and application developers, to business leaders and IT infrastructure managers, in addition to students and researchers. Dr. Zaigham Mahmood is Reader in Applied Computing and Assistant Head of the Distributed and Intelligent Systems Research Group at the School of Computing in the University of Derby, UK. Dr. Richard Hill is Head of Subject (Computing and Mathematics) and Reader in Intelligent Systems at the School of Computing in the University of Derby, UK.